Crowded Orbits: Conflict and Cooperation in Space - JAMES CLAY MOLTZ (Columbia University Press, 2014)
Competing nations have thus far managed to avoid direct conflict in space. Given past battles over land territories, on the world’s oceans, and in the air, the record of humans in space since the first satellite launch in 1957 is impressive. But will countries be able to keep the peace as space becomes more crowded? This is a simple and yet very important question that requires greater attention. In the 1960s television program Star Trek, the countries of the world finally, by the twenty-second century, develop a cooperative organization for working together in space, the United Federation of Planets. It includes all people on Earth and also beings from friendly planets. But the route to the federation, as described in the program, was a very costly one: nuclear war on Earth, battles in space, and only an ex post facto recognition that the nations on Earth had fundamentally shared interests as they explored the galaxies. Like the rapprochements in real life that ended the prior divisions within Western Europe after 1945 and between Western and Eastern Europe after 1989, this basic revelation had taken many years of conflict to be realized. In the Star Trek television series, international cooperation comes about only under the threat of the end of human civilization—almost as a last resort. If the nuclear wars that took place had gone worse, this cooperative escape route might have been snuffed out entirely. This fictional metaphor is hardly a positive one for the coming generations of people on this planet or for the next few hundred years in space. Can we do better? If so, how? The risk of space conflict raises a number of troubling challenges as we stand on the threshold of a major expansion of human space activity. In order to prevent space warfare, we will need to understand the preconditions for bringing about greater collaboration among Earth’s nations in orbit. Can we achieve cooperation sooner than in the Star Trek series and without having to go through the possibly disastrous effects of nuclear or space war? Might successful cooperation in near- Earth space—such as on the International Space Station (ISS)—serve as a first step? Perhaps, but the current space station does not include a number of important new spacefaring countries. Also, recent destructive activities in low-Earth orbit by China and the United States and threats by other nations to develop similar anti-satellite capabilities presage difficulties in overcoming international mistrust in space.